Formation and Regeneration of Methanococcus voltae Protoplasts - Patel, G. B. (1993)
Methanococcus voltae cells were converted into protoplasts by suspension in anaerobic 0.1 M Tris-HCl buffer containing 0.4 M sucrose and 0.05 M NaCl as osmoprotectants. Protoplast formation was monitored microscopically by observing the conversion of the typical irregularly shaped (uneven peripheries) coccoid whole cells to rounded forms with smooth peripheries. Although the procedure resulted in about 50% lysis of the initial number of cells, the remainder were converted to the rounded form. Analysis by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and electron microscopy of negatively stained cell preparations indicated that the treatment removed the wall layer from whole cells to yield protoplasts. Protoplast regeneration was evaluated by using optimized plating conditions and an anaerobic microplating technique. Between 50 and 63% of the initial number of protoplasts regenerated as colonies on agar medium (35°C, 7 days). The colony and cell morphologies of the regenerated protoplasts were indistinguishable from those of whole cells plated under identical conditions.